Green corridor: A critical perspective and development of research agenda - Aman, Aini; Rafiq, Muhammad; Dastane, Omkar; Sabir, Asrar Ahmed (Frontiers in Environmental Science, 2022)
The rapid development of industrialization, transportation, and urbanization has a negative impact on nature such as increased pollution, decreased pervious surface area, and increased temperatures. Researchers are consistently trying to find out the ways, which can facilitate the reduction of naturally unfriendly impacts. In this context, ‘green corridors’ play a critical role. The main goal of the ‘green corridors’ is to help build sustainable industrial, urban, and transportation networks by meeting requirements for environmental, technical, economic, social, and space planning issues. This paper provides a critical perspective on extant ‘green corridor’ research by analysing its performance and unwinding the intellectual structure. The perspective also sheds light on gaps in current literature and therefore, possible future research avenues and calls for research in the field of ‘green corridor’.